PENGARUH KONSENTRASI DAN INTERVAL PEMBERIAN PUPUK ORGANIK CAIR TERHADAP PERTUMBUHAN DAN HASIL TANAMAN KACANG MERAH (Phaseolus vulgaris L.) DALAM POLYBAG - Arnoldus Herdi Yanto; Yacobus Sunaryo; Sri Widata (JURNAL ILMIAH AGROUST, 2018)
This research was conducted to determine the optimal of concentration and application interval of liquid organic fertilizer (LOF) in the growth and yield of red beans (phaseolus vulgaris L). The research was carried out in Pusat Pelatihan Pertanian dan Pedesaan Swadaya (P4S) â€œLestari Makmurâ€ Located In Wates Street Km 12 Polaman, Argorejo Village, Sedayu District, Bantul Regency, Special Region Of Yogyakarta.Â  The research was conducted by 3 x 2 + 1 factorial experiment arranged in Completely Randomized Design (CRD). The first factor was the concentration Of Liquid Organic Fertilizer (LOF) consists of 3 levels namely: 1%, 2%, and 3%. The second factor was interval of Liquid Organic Fertilizer application consists of 2 levels: once week watering and watering every 2 weeks.Â  The result of this experiment indicated that there was no interaction between concentration and interval application of Liquid Organic Fertilizer (LOF) on plant height, plant dry weight, flowers number, pods number, pod dry weight and pod length. Interval application of Liquid Organic Fertilizer (POC) had significantly effect on pod length and plant dry weight